Transcatheter arterial embolization for intercostal arterial bleeding in a patient after chest tube insertion - Chen, Ren-Biao; Hu, Hong-Jie; Matro, Erik (Journal of Thoracic Disease; Vol 7, No 7 (July 30, 2015): Journal of Thoracic Disease, 2015)
Retrograde tube radiography is commonly used in cholangiography and pyelography. We present a case of massive chest tube bleeding 10 days after tube insertion with no noted contrast extravasation on contrast enhanced chest CT with active bleeding detected by retrograde radiography via the chest tube. Subsequent transcatheter arterial embolization (TAE) was successfully performed as a definitive treatment to stop active bleeding. We consider that retrograde tube radiography may be an alternative diagnostic method for patients with active bleeding from a drainage tube, helping to localize bleeding points and presenting TAE an attractive, minimally invasive and effective treatment modality for intercostal artery rupture.